Preoperative surveillance rectal swab is associated with an increased risk of infectious complications in pancreaticoduodenectomy and directs antimicrobial prophylaxis: an antibiotic stewardship strategy?. Issue 6 (June 2018) - De Pastena, Matteo; Paiella, Salvatore; Azzini, Anna M.; Marchegiani, Giovanni; Malleo, Giuseppe; Ciprani, Debora; Mazzariol, Annarita; Secchettin, Erica; Bonamini, Deborah; Gasparini, Clizia; Concia, Ercole; Bassi, Claudio; et al.
Abstract: Background: Despite improvements in the perioperative care, the morbidity rate after pancreaticoduodenectomy (PD) is still higher than 50%. The aim of this study was twofold: first, to assess the correlation between preoperative rectal swab (RS) and intraoperative bile cultures; to examine the impact of RS isolates on postoperative course after PD. Methods: An observational study was conducted analyzing all consecutive PD performed from January 2015 to July 2016. Based on the positivity/negativity of preoperative RS for multi-drug resistant bacteria, two groups of patients were identified (RS+ vs. RS−) and then compared. Results: Three hundred thirty-eight patients were considered for the analysis. RS culture showed a perfect correlation (species and phenotypic antibiotic susceptibility pattern) with bile culture in 157 patients (86.7%). Fifty patients (14.8%) had a RS+. Preoperative biliary drain (PBD) was the single independent preoperative risk factor associated to RS+ (p = 0.021, OR = 2.6, 95% CI = 1.5–11.7). Infective complications (IC) and mortality were independently correlated to RS+ (p = 0.013, OR = 2.9, 95% CI = 1.3–6.7; p = 0.009 OR = 3.4, 95% CI = 1.8–14.9, respectively). Conclusions: Preoperative surveillance RS-culture's positivity correlates to biliary colonization that occurs after PBD. IC and mortality after PD are associated with RS+. Preoperative RS can direct antibiotic prophylaxis to reduce morbidity and mortality after PD.